Spiral Bevel Gears Face Roughness Prediction Produced by CNC End Milling Centers - Álvaro Álvarez (Materials, 2018)
The emergence of multitasking machines in the machine tool sector presents new opportunities for the machining of large size gears and short production series in these machines. However, the possibility of using standard tools in conventional machines for gears machining represents a technological challenge from the point of view of workpiece quality. Machining conditions in order to achieve both dimensional and surface quality requirements need to be determined. With these considerations in mind, computer numerical control (CNC) methods to provide useful tools for gear processing are studied. Thus, a model for the prediction of surface roughness obtained on the teeth surface of a machined spiral bevel gear in a multiprocess machine is presented. Machining strategies and optimal machining parameters were studied, and the roughness model is validated for 3 + 2 axes and 5 continuous axes machining strategies.